Dukungan Suami dan Kepuasan Kerja yang Dimediasi oleh Konflik Pekerjaan-Keluarga pada Ibu yang Bekerja - Triana Noor E. D. Soeharto; Muhammad Wahyu Kuncoro (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This study aimed to assess the effect of spousal support on job satisfaction of working mothers moderated by work-family conflict. The characteristics of the subjects of this study were (1) living with a partner and children under 12 years old and (2) working full-time. This research used four variables: job satisfaction, husband’s support, work- family conflict, family-work conflict. Based on the results of analysis using structural equation model for the variables of husband’s support, work-family conflict, family-work conflict and job satisfaction, chi-square scored 0.070 with p = 0.791. Based on the predetermined criteria, the chi-square scored with p>0.05, GFI≥0.90, AGFI≥0.90. The analysis revealed that the results of the fittingness test had met the criteria. Based on these results it can be concluded that the hypothesis of this study is accepted, showing that husband’s support has effect on job satisfaction mediated by work-family conflict in a working mother.